PENGARUH MEKANISME CORPORATE GOVERNANCE PADA MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2013) - Dwi Nofiana, 12.05.52.0116; Maryono, Maryono (Students Journal of Accounting and Banking, 2016)
This study examine the influence of independent directors , company size , managerial ownership and institutional ownership to earnings management, This research was conducted at a manufacturing company in Indonesia Stock Exchange 2010-2013. The sampling method in this study using purposive sampling method with the research period 2010 to 2013. The data used in this study is data from manufacturing companies that met the selection criteria. The analytical method used in this research is multiple regression analysis. Research shows that the proportion of independent board significant negative effect and the size of the company significant positive effect on earnings management. While the positive effect of managerial ownership and institutional ownership has no significant negative effect is not significant.Keywords: Independent Directors, Company Size, Managerial Ownership, Institutional Ownership, Profit Management